2020
DOI: 10.1038/s41598-020-69969-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and brain plasticity in a rat model of shift work: role of daily rhythms, sleep and glucocorticoids

Abstract: Many occupations require operations during the night-time when the internal circadian clock promotes sleep, in many cases resulting in impairments in cognitive performance and brain functioning. Here, we use a rat model to attempt to identify the biological mechanisms underlying such impaired performance. Rats were exposed to forced activity, either in their rest-phase (simulating night-shift work; rest work) or in their active-phase (simulating day-shift work; active work). Sleep, wakefulness and body tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…This study is a phase II clinical trial, which limits generalizability to a larger population. Individual variability in tolerance for shift work 67 was also not evaluated in this study and should be taken into account before prescribing exogenous melatonin. However, the longitudinal crossover design in real-life conditions is the strength of this study.…”
Section: Marqueze Et Almentioning
confidence: 99%
“…This study is a phase II clinical trial, which limits generalizability to a larger population. Individual variability in tolerance for shift work 67 was also not evaluated in this study and should be taken into account before prescribing exogenous melatonin. However, the longitudinal crossover design in real-life conditions is the strength of this study.…”
Section: Marqueze Et Almentioning
confidence: 99%
“…The putamen is a known site of synaptic plasticity ( Kreitzer and Malenka, 2008 ), and it has been reported that circadian rhythms affect the plasticity of putamen ( Elmenhorst et al, 2016 ). Animal studies have demonstrated that simulated shift work impairs the synthesis of proteins related to synaptic plasticity ( Marti et al, 2017 , 2020 ). A decrease in the level of melatonin in shift workers ( Wei et al, 2020 ) may contribute to the impaired neuroplasticity in this group, as melatonin is known to stimulate all stages of neuroplasticity ( Valdés-Tovar et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…One such example of chronic circadian disruption occurs in shift work, which puts individuals at a higher risk for cardiovascular disease, diabetes, affective disorders, obesity, fertility issues, cancer, and more ( Costa, 2010 ). Rodents that underwent a paradigm mimicking human shift work also showed many of these same negative and persistent effects ( Marti et al, 2020 ; Banks et al, 2022 ).…”
Section: Acute and Chronic Effects Of Disruptions In Sleep And Circad...mentioning
confidence: 97%